Response of soybean cultivars to the reduction of plant density in the northern plateau of Santa Catarina - Deretti, André Felipe Hermann; Sangoi, Luis; Martins Junior, Marcos Cardoso; Gularte, Paulo Sérgio; Castagneti, Valdeci; Leolato, Lucieli Santini; Kuneski , Hugo François; Scherer, Rafael Leandro; Berkenbrock, Jardel; Duarte, Lucas; et al. (Revista de Ciências Agroveterinárias, 2022)
The plant density is a relevant management practice to obtain high yields in soybean (Glycine max (L) Merrill). The tendency to decrease the plant population is increasing due to the high cost of seeds. Thus, the objective of the present study was to evaluate the agronomic performance of different soybean cultivars to the reduction in plant density in the North Plateau of Santa Catarina. The experimental design was randomized blocks arranged in split plots. In the main plots, five cultivars were evaluated: AS3590 IPRO, BMX Ativa RR, BMX Zeus IPRO, M5838 IPRO, and NS5445 IPRO. The subplots evaluated four population densities: 120,000 plants ha-1, 160,000 plants ha-1, 200,000 plants ha-1 and the control (density indicated by the cultivar holder). Grain yield evaluations and their components were performed and the data was submitted to analysis of variance using the F test. When significant, the means of the main effects were compared by the Tukey test. In case of interaction, the means were then compared by regression analysis. Both comparisons were at the 5% significance level. The reduction in plant population did not affect the number of pods per area, the number of grains per pod, the harvest index, and grain yield. On the other hand, reducing plant density increased the number of pods on the branches and per plant. Therefore, the tested soybean cultivars supported reductions in plant population without affecting grain yield and productivity. In this way, reducing plant density can be recommended for soybean cultivated in the North Plateau of Santa Catarina.